Piezoelectric single crystal, its manufacturing method, and piezoelectric and dielectric application parts using the same
A piezoelectric single crystal with a perovskite structure, manufactured using a solid phase growth method and specific compositions, addresses limitations of existing crystals by enhancing dielectric and piezoelectric properties and mechanical durability, enabling wide temperature and voltage use with cost-effective mass production.
Patent Information
- Application Number
- JP2023534611
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-12-03
- Filing Date
- 2021-12-08
- Publication Date
- 2025-01-22
- Estimated Expiration
- 2041-12-08
AI Technical Summary
Existing piezoelectric single crystals with a perovskite crystal structure face limitations such as low phase transition temperatures, low coercive electric fields, brittleness, and high production costs, which restrict their operating temperature range, voltage conditions, and mechanical durability, making them unsuitable for high-performance applications.
A piezoelectric single crystal with a perovskite structure is developed using a solid phase single crystal growth method, with specific chemical compositions and a reinforcing second phase, achieving high dielectric and piezoelectric constants, improved mechanical properties, and uniform composition, and allowing for mass production.
The new piezoelectric single crystal exhibits high dielectric and piezoelectric properties, withstands mechanical impact, and can be used in a wide temperature and voltage range, suitable for high-performance applications with reduced production costs.
Smart Images

Figure 0007619681000001 
Figure 0007619681000002 
Figure 0007619681000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a piezoelectric single crystal, a method for producing the same, and piezoelectric and dielectric application parts using the piezoelectric single crystal. More specifically, the present invention relates to a piezoelectric single crystal having a perovskite crystal structure ([A][B]O3), and the characteristics of the piezoelectric single crystal are improved by controlling the composition of the [A] site ions, thereby achieving a high dielectric constant (K3 T ≧4,000~15,000), high piezoelectric constant (d 33 ≧1,400~6,000pC / N), high coercive field (E C The present invention relates to a piezoelectric single crystal having a perovskite crystal structure which simultaneously realizes a resistivity of 100 V to 400 V (≥ 4 to 12 kV / cm) and which, by being produced by a solid-phase single crystal growth method, provides a uniform piezoelectric single crystal without a composition gradient even in the case of a complex chemical composition, and which also has mechanical properties, a method for producing the same, and piezoelectric and dielectric application parts which use the piezoelectric single crystal. [Background technology]
[0002] Piezoelectric single crystals with a perovskite crystal structure ([A][B]O3) have a much higher dielectric constant (K3 T ) and the piezoelectric constant (d 33 and k 33 ) and are used in high-performance parts such as piezoelectric actuators, ultrasonic transducers, piezoelectric sensors, and dielectric capacitors, and are also expected to be used as substrate materials for various thin-film elements.
[0003] Among the piezoelectric single crystals with perovskite crystal structure developed to date, PMN-PT(Pb(Mg 1 / 3 Nb 2 / 3 )O3-PbTiO3), PZN-PT(Pb(Zn 1 / 3 Nb 2 / 3 )O3-PbTiO3), PInN-PT(Pb(In 1 / 2 Nb 1 / 2 )O3-PbTiO3), PYbN-PT(Pb(Yb 1 / 2 Nb 1 / 2 )O3-PbTiO3), PSN-PT(Pb(Sc 1 / 2 Nb 1 / 2)O3-PbTiO3), PMN-PInN-PT, PMN-PYbN-PT, and BiScO3-PbTiO3 (BS-PT). These single crystals exhibit congruent melting behavior during melting, and are usually manufactured by existing single crystal growth methods such as the flux method and the Bridgman method.
[0004] However, the previously developed PMN-PT and PZN-PT piezoelectric single crystals have high dielectric and piezoelectric properties (K3 T >4,000, d 33 >1,400pC / N, k 33 >0.85), but has a low phase transition temperature (T C and T RT ), low coercive field (E C ) and brittleness, the temperature range and voltage conditions under which the piezoelectric single crystal can be used, as well as the conditions for manufacturing components using the piezoelectric single crystal, are significantly restricted.
[0005] In general, it is known that a piezoelectric single crystal having a perovskite crystal structure has the highest dielectric and piezoelectric properties in the region near the phase boundary between the rhombohedral phase and the tetragonal phase, that is, the MPB (morphotropic phase boundary) composition.
[0006] However, piezoelectric single crystals with a perovskite crystal structure generally exhibit the best dielectric and piezoelectric properties when they are in the rhombohedral phase, and therefore, applications of rhombohedral phase piezoelectric single crystals are the most active. However, the phase transition temperature (T RT ) below which the rhombohedral phase exhibits stable behavior, the maximum temperature at which the rhombohedral phase exhibits stable behavior is T RT Its use is possible only in the following cases: RT When the phase transition temperature is low, the operating temperature of the rhombohedral phase piezoelectric single crystal is low, and the manufacturing temperature and operating temperature of the piezoelectric single crystal application parts are also low. RT It is limited to the following:
[0007] In addition, the phase transition temperature (T C and T RT ) and coercive electric field (E C If the phase transition temperature (T C and T RT ) and coercive electric field (E C ) piezoelectric single crystals have limitations on the manufacturing conditions, operating temperature conditions, and driving voltage conditions of single crystal application parts. In the case of PMN-PT single crystals, T C <150℃, T RT <80°C, and E C <2.5 kV / cm, and for PZN-PT single crystals, T C <170℃, T RT <100°C and E C <3.5 kV / cm. In addition, dielectric and piezoelectric application parts made of such piezoelectric single crystals are also limited in terms of manufacturing conditions, operating temperature range, operating voltage conditions, etc., which have been an obstacle to the development and practical application of piezoelectric single crystal application parts.
[0008] To overcome the shortcomings of piezoelectric single crystals, single crystals with new compositions such as PInN-PT, PSN-PT, and BS-PT have been developed, and mixed single crystal compositions such as PMN-PInN-PT and PMN-BS-PT have also been investigated.
[0009] However, in the case of such single crystals, it is not possible to simultaneously improve the dielectric constant, piezoelectric constant, phase transition temperature, coercive field, and mechanical properties, and the like, and the high manufacturing cost of piezoelectric single crystals consisting mainly of expensive elements such as Sc and In has been an obstacle to the practical use of single crystals.
[0010] There are three main reasons why piezoelectric single crystals with perovskite crystal structures, including PMN-PT, developed to date exhibit low phase transition temperatures. The first is that the phase transition temperature of the relaxor (PMN, PZN, etc.), which is the main component along with PT, is low.
[0011] Non-Patent Document 1 reports the phase transition temperature (T C ) are presented in Table 1. Since the Curie temperature of a piezoelectric single crystal is almost the same as that of a polycrystalline body of the same composition, the Curie temperature of the piezoelectric single crystal can be estimated from the Curie temperature of the polycrystalline body.
[0012] Second, the MPB, which is the boundary between the tetragonal and rhombohedral phases, is not perpendicular to the temperature axis but is gently tilted, and the phase transition temperature (T RT In order to increase the Curie temperature (T C ) is essential, so the Curie temperature (T C ), and the phase transition temperature between the rhombohedral and tetragonal phases (T RT ) at the same time.
[0013] Third, when a relaxor with a relatively high phase transition temperature (such as PYbN, PInN, or BiScO3) is mixed into PMN-PT, the phase transition temperature does not simply increase in proportion to the composition, or the dielectric and piezoelectric properties deteriorate.
[0014] Furthermore, the Relaxor-PT type single crystals presented in Non-Patent Document 1 are produced by existing single crystal growth methods such as the flux method and the Bridgman method, which mainly use a melting process. However, due to reasons related to the single crystal production process, it is difficult to produce large single crystals with a uniform composition, and the production costs are high and mass production is difficult, so they have not yet been successfully commercialized.
[0015] In addition, piezoelectric ceramic single crystals generally have a disadvantage in that they are easily broken even by small mechanical shocks because they have lower mechanical strength and fracture toughness than piezoelectric ceramic polycrystalline bodies. The brittleness of piezoelectric single crystals tends to induce breakage of the piezoelectric single crystals during the manufacture and use of application parts using the piezoelectric single crystals, which has been a major limitation in the use of piezoelectric single crystals. Therefore, in order to commercialize piezoelectric single crystals, it is necessary to improve the mechanical properties of the piezoelectric single crystals as well as the dielectric and piezoelectric properties of the piezoelectric single crystals.
[0016] Here, the inventors have made continuous efforts to improve the conventional problems and provide a piezoelectric single crystal of a level applicable to the high-performance, high-precision, high-added-value market. As a result, it was found that the piezoelectric properties improve as the chemical composition constituting the piezoelectric single crystal becomes more complex. In order to improve the piezoelectric properties of the single crystal, the inventors designed the composition of the [A] site ions in the perovskite crystal structure ([A][B]O3) and confirmed the production of a piezoelectric single crystal that is uniform, has improved piezoelectric properties, and also has mechanical properties, without a composition gradient, even with a complex chemical composition, by using a solid-phase single crystal growth method, thereby completing the present invention. [Prior art documents] [Patent documents]
[0017] [Patent Document 1] Republic of Korea Patent No. 0564092 (published on March 27, 2006) [Patent Document 2] Republic of Korea Patent No. 0743614 (published on 2007.07.30) [Non-patent literature]
[0018] [Non-Patent Document 1] IEEE Transactions on Ultrasonics, Ferroelectrics, and Frequency Control, vol. 44, no. 5, 1997, pp. 1140-1147. Summary of the Invention [Problem to be solved by the invention]
[0019] An object of the present invention is to provide a piezoelectric single crystal having a perovskite-type crystal structure ([A][B]O3) with a novel composition formula.
[0020] Another object of the present invention is to provide a method for producing the piezoelectric single crystal.
[0021] It is still another object of the present invention to provide a piezoelectric component and a dielectric component using the piezoelectric single crystal. [Means for solving the problem]
[0022] In order to achieve the above object, the present invention provides a piezoelectric single crystal having a composition formula of Chemical Formula 1 below.
[0023] chemical formula 1 [A 1-(a+1.5b) B a C b ][(MN) 1-x-y (L) y Ti x ]O3 In the above formula, A is Pb or Ba, B is at least one selected from the group consisting of Ba, Ca, Co, Fe, Ni, Sn, and Sr; C is at least one selected from the group consisting of Co, Fe, Bi, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu; L is selected from Zr or Hf, either alone or in a mixed form; M is at least one selected from the group consisting of Ce, Co, Fe, In, Mg, Mn, Ni, Sc, Yb, and Zn; N is at least one selected from the group consisting of Nb, Sb, Ta, and W; 0 <a≦0.10、 0 <b≦0.05、 0.05≦x≦0.58, 0.05≦y≦0.62.
[0024] In this case, when L is in a mixed form, a piezoelectric single crystal having a composition formula of the following Chemical Formula 2 is provided.
[0025] chemical formula 2 [A 1-(a+1.5b) B a C b ][(MN) 1-x-y (Zr 1-w ,Hf w ) y Ti x ]O3 In the formula, A, B, C, M, and N are the same as those in Chemical Formula 1, and a, b, x, and y are also the same, with the proviso that 0.01≦w≦0.20.
[0026] The piezoelectric single crystal having the composition formula of Chemical Formula 1 of the present invention has a composition that satisfies 0.01≦a≦0.10 and 0.01≦b≦0.05, and more preferably satisfies a / b≧2 in the above formulas.
[0027] It is more preferable that the piezoelectric single crystal having the composition formula of Chemical Formula 1 of the present invention satisfies 0.10≦x≦0.58 and 0.10≦y≦0.62.
[0028] In addition, the piezoelectric single crystal having the composition formula of Chemical Formula 1 of the present invention has a composition gradient of 0.2 to 0.5 mol % within the single crystal, which gives it a homogeneous characteristic.
[0029] The composition of the piezoelectric single crystal may further include 0.1 to 20% by volume of a reinforcing second phase (P), the reinforcing second phase P being a metal phase, an oxide phase, or pores.
[0030] More specifically, the reinforcing second phase P is at least one selected from the group consisting of Au, Ag, Ir, Pt, Pd, Rh, MgO, ZrO2, and pores, and the reinforcing second phase P is distributed uniformly in particulate form or regularly distributed in a certain pattern within the piezoelectric single crystal.
[0031] In addition, in the piezoelectric single crystal, the x and y are within a range of 10 mol % of the composition of the phase boundary (MPB) between the rhombohedral phase and the tetragonal phase, and more preferably, the x and y are within a range of 5 mol % of the composition of the phase boundary (MPB) between the rhombohedral phase and the tetragonal phase.
[0032] The above piezoelectric single crystals have a Curie temperature (T C ) is 180°C or higher, and the phase transition temperature between rhombohedral phase and tetragonal phase (T RT ) is 100°C or higher.
[0033] In addition, the piezoelectric single crystal has an electromechanical coupling coefficient (longitudinal electromechanical coupling coefficient, k 33 ) is 0.85 or more, and the coercive electric field (E C ) satisfies 3.5 to 12 kV / cm.
[0034] In particular, the piezoelectric single crystal has a dielectric constant (K T ) 4,000 to 15,000, and the piezoelectric constant (d 33 ) Meets 1,400 to 6,000 pC / N.
[0035] The present invention provides a method for producing the piezoelectric single crystal, comprising the steps of: (a) adjusting the average size of matrix grains of the polycrystalline body having the composition to reduce the number density of abnormal grains (number of abnormal grains / unit area); (b) a step of heat-treating the polycrystalline body with a reduced number density of abnormal grains obtained by step (a) to grow the abnormal grains, the method comprising a primary heat treatment step of calcining a powder having a composition constituting the piezoelectric single crystal at a temperature of 800 to 900°C to obtain a powder compact, and sintering the powder compact, and a secondary heat treatment step during the growth of the single crystal.
[0036] As another manufacturing method, there is provided a method for manufacturing a piezoelectric single crystal, which comprises adjusting the average grain size of matrix grains of a polycrystalline body having the above composition and heat-treating the polycrystalline body under conditions for reducing the number density of abnormal grains.
[0037] In the above, it is possible to obtain a single crystal by continuing to grow only the small number of abnormal grains that have been generated in a state where the number density of abnormal grains in the polycrystalline body has been reduced.
[0038] A method for producing a piezoelectric single crystal can be provided in which a seed single crystal is bonded to the polycrystalline body before the heat treatment of the polycrystalline body, and the seed single crystal continues to grow within the polycrystalline body during the heat treatment. In this case, the average grain size (R) of the matrix grains of the polycrystalline body is set to a critical grain size at which abnormal grains are generated (the average grain size of the matrix grains at which the number density of abnormal grains becomes "0 (zero)", R C ) to 2 times the size range (0.5R C ≦R≦2R C ) is adjusted within
[0039] Furthermore, the present invention provides piezoelectric application parts and dielectric application parts using a piezoelectric body made of the piezoelectric single crystal, or a piezoelectric body made by combining the piezoelectric single crystal with a polymer.
[0040] The piezoelectric application parts and dielectric application parts using the piezoelectric material may be any one selected from the group consisting of ultrasonic transducers, piezoelectric actuators, piezoelectric sensors, dielectric capacitors, electric field generating transducers, and electric field and vibration generating transducers. Effect of the Invention
[0041] The piezoelectric single crystal of the present invention has a high dielectric constant (K3 T ), high piezoelectric constant (d 33 and k 33 ), high phase transition temperature (T C and T RT ), and high coercive electric field (E C ) can significantly improve the dielectric properties.
[0042] In addition, the piezoelectric single crystal of the present invention has a uniform chemical composition without a composition gradient even though it is a compound composition formed by the solid phase single crystal growth method, and the piezoelectric properties can be improved. In addition, due to the pores generated during the solid phase single crystal growth method, the piezoelectric single crystal has high resistance to mechanical shock, and a manufacturing method can be provided that can provide the piezoelectric single crystal in a form that is easy to machine.
[0043] Furthermore, the present invention has the advantage of being able to be used in a wide range of temperatures and voltage conditions while also having good mechanical properties, and can be applied to fields that require high added value such as high performance and high precision due to its high dielectric properties.
[0044] Therefore, a solid-phase single crystal growth method suitable for mass production of single crystals is used to manufacture piezoelectric single crystals, and a single crystal composition that does not contain expensive raw materials is developed, making it possible to commercialize piezoelectric single crystals. The application parts according to the present invention use piezoelectric single crystals with excellent characteristics, and can be used to manufacture piezoelectric application parts and dielectric application parts over a wide temperature range. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0045] The present invention will be described in detail below.
[0046] The present invention provides a piezoelectric single crystal having a composition formula of Chemical Formula 1 below.
[0047] chemical formula 1 [A 1-(a+1.5b) B a C b ][(MN) 1-x-y (L) y Ti x ]O3 In the above formula, A is Pb or Ba, B is at least one selected from the group consisting of Ba, Ca, Co, Fe, Ni, Sn, and Sr; C is at least one selected from the group consisting of Co, Fe, Bi, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu; L is selected from Zr or Hf, either alone or in a mixed form; M is at least one selected from the group consisting of Ce, Co, Fe, In, Mg, Mn, Ni, Sc, Yb, and Zn; N is at least one selected from the group consisting of Nb, Sb, Ta, and W; 0 <a≦0.10、 0 <b≦0.05、 0.05≦x≦0.58, 0.05≦y≦0.62.
[0048] The piezoelectric single crystal having the composition formula of Chemical Formula 1 of the present invention has a complex composition of [A] site ions in a perovskite crystal structure ([A][B]O3) based on the tendency that the piezoelectric properties are further increased as the chemical composition is complexed.
[0049] In this case, in the piezoelectric single crystal having the composition formula of Chemical Formula 1, the composite composition of the [A] site ions is specifically as follows: 1-(a+1.5b) B a C b The composition of A may include lead-containing or lead-free elements. In the embodiments of the present invention, the description will be limited to a lead-containing piezoelectric single crystal in which A is Pb, but the present invention is not limited thereto.
[0050] In the [A] site ion, the B composition is a divalent metal element, preferably at least one selected from the group consisting of Ba, Ca, Co, Fe, Ni, Sn, and Sr, and the C composition can be any trivalent metal element.
[0051] Preferably, it is at least one selected from the group consisting of Co, Fe, Bi, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu, and more preferably, the lanthanum-based element is used in a mixed form of one or two kinds.
[0052] In the examples of the present invention, the C composition in the [A] site ion is described as a single composition or a mixed composition of at least one of La, Sm, and Bi, but is not limited thereto.
[0053] In the composite composition of the [A] site ions in the piezoelectric single crystal having the composition formula of Chemical Formula 1, [A 1-(a+1.5b) B a C b The composition of the formula [1] is characterized in that, as a requirement for realizing the target physical properties, when A is a lead-containing or lead-free piezoelectric single crystal, it is composed of a combination of a divalent metal element and a trivalent metal element.
[0054] That is, the following conditions must be satisfied: 0.01≦a≦0.10 and 0.01≦b≦0.05, and more preferably a / b≧2. In this case, if a is less than 0.01, there is a problem that the perovskite phase is unstable, and if it exceeds 0.10, the phase transition temperature becomes too low, making practical use difficult, which is undesirable.
[0055] Also, if the requirement of a / b≧2 is not met, the dielectric and piezoelectric properties are not maximized, or the growth of single crystals is limited.
[0056] In this case, in the composite composition of the [A] site ions in the piezoelectric single crystal having the composition formula of Chemical Formula 1, a superior dielectric constant can be achieved compared to the case where the composite composition is composed of a single metal trivalent element or a single metal divalent element.
[0057] The commonly known [A][MN]O3-PbTiO3-PbZrO3 phase diagram shows a composition region that exhibits excellent dielectric and piezoelectric properties around the phase boundary (MPB) between the rhombohedral phase and the tetragonal phase. In the [A][MN]O3-PbTiO3-PbZrO3 phase diagram, the dielectric and piezoelectric properties are maximum in the phase boundary composition region between the rhombohedral phase and the tetragonal phase, and the dielectric and piezoelectric properties gradually decrease as they move away from the MPB composition region. In the composition range from the MPB composition region to within 5 mol% into the rhombohedral phase region, the decrease in the dielectric and piezoelectric properties is small and very high dielectric and piezoelectric property values are maintained, and in the composition range from the MPB composition region to within 10 mol% into the rhombohedral phase region, the dielectric and piezoelectric properties continue to decrease, but are still high enough to be applied to dielectric and piezoelectric application parts. When the composition changes from the MPB composition region into the tetragonal phase region, the dielectric and piezoelectric properties decrease more rapidly than when the composition changes into the rhombohedral phase region. However, even when the composition ranges within 5 mol % or 10 mol % into the tetragonal phase region, the dielectric and piezoelectric properties continue to decrease, but the dielectric and piezoelectric properties are still high enough to be used in dielectric and piezoelectric application parts.
[0058] The phase boundary (MPB) between PbTiO3 and PbZrO3 is known as PbTiO3:PbZrO3 = x:y = 0.48:0.52 (molar ratio).
[0059] When the composition changes 5 mol % from the MPB region into the rhombohedral phase region and into the tetragonal phase region, the maximum values of x and y are 0.53 and 0.57, respectively (in other words, when x is at its maximum, x:y=0.53:0.47, and when y is at its maximum, x:y=0.43:0.57).When the composition changes 10 mol % from the MPB region into the rhombohedral phase region and into the tetragonal phase region, the maximum values of x and y are 0.58 and 0.62, respectively (in other words, when x is at its maximum, x:y=0.58:0.42, and when y is at its maximum, x:y=0.38:0.62). In the composition range of 5 mol % or less from the MPB composition region into the rhombohedral phase region and into the tetragonal phase region, respectively, high dielectric and piezoelectric property values are maintained, and in the composition range of 10 mol % or less from the MPB composition region into the rhombohedral phase region and into the tetragonal phase region, respectively, dielectric and piezoelectric property values that are sufficiently high for application to dielectric and piezoelectric application components are exhibited.
[0060] In addition, when the contents of PbTiO3 and PbZrO3, i.e., the values of x and y, are less than 0.05, the phase boundary between the rhombohedral phase and the tetragonal phase cannot be formed, or the phase transition temperature and the coercive field are too low to be suitable for the present invention.
[0061] In the above formula 1, preferably, 0.05≦x≦0.58, and more preferably, 0.10≦x≦0.58. In this case, when x is less than 0.05, the phase transition temperature (T C and T RT ), piezoelectric constant (d 33 , k 33 ) or coercive electric field (E C ) is low and x exceeds 0.58, the dielectric constant (K3 T ), piezoelectric constant (d 33 , k 33) or phase transition temperature (T RT ) is low.
[0062] Meanwhile, in the above Chemical Formula 1, preferably, 0.05≦y≦0.62 is satisfied, and more preferably, 0.10≦y≦0.62 is satisfied. The reason is that when y is less than 0.05, the phase transition temperature (T C and T RT ), piezoelectric constant (d 33 , k 33 ) or coercive electric field (E C ) is low and exceeds 0.62, the dielectric constant (K3 T ) or the piezoelectric constant (d 33 , k 33 ) is low.
[0063] The piezoelectric single crystal having the composition formula of Chemical Formula 1 of the present invention contains a tetravalent metal element in the [B] site ion in the perovskite crystal structure ([A][B]O3), but in particular, the L composition is limited to a single or mixed form selected from Zr and Hf.
[0064] In the case of the mixed form, a piezoelectric single crystal having a composition formula of Chemical Formula 2 below is provided.
[0065] chemical formula 2 [A 1-(a+1.5b) B a C b ][(MN) 1-x-y (Zr 1-w ,Hf w ) y Ti x ]O3
[0066] In the formula, A, B, C, M, and N are the same as those in Chemical Formula 1, and a, b, x, and y are also the same, with the proviso that 0.01≦w≦0.20.
[0067] At this time, if w is less than 0.01, the dielectric and piezoelectric properties are not maximized, whereas if it exceeds 0.20, the dielectric and piezoelectric properties are rapidly degraded, which is undesirable.
[0068] The piezoelectric single crystal having the composition formula of Chemical Formula 1 above has a perovskite crystal structure ([A][B]O3), and by combining the composite composition of [A] site ions and the composition of [B] site ions, it is possible to obtain a high Curie temperature (T C ) is 180°C or higher, and at the same time, the phase transition temperature between the rhombohedral phase and the tetragonal phase (T RT ) is 100°C or higher. In this case, if the Curie temperature is less than 180°C, the coercive electric field (E C ) at 5 kV / cm or higher or at the phase transition temperature (T RT ) is difficult to raise above 100°C.
[0069] In addition, the piezoelectric single crystal having the composition formula of Chemical Formula 1 according to the present invention has an electromechanical coupling coefficient (k 33 If the electromechanical coupling coefficient is 0.85 or more and the electromechanical coupling coefficient is less than 0.85, the properties become similar to those of piezoelectric polycrystalline ceramics, and the energy conversion efficiency becomes low, which is not preferable.
[0070] The piezoelectric single crystal of the present invention has a coercive electric field (E C If the coercive electric field is less than 3.5 kV / cm, there is a problem that poling is easily removed during processing of the piezoelectric single crystal or during manufacture or use of piezoelectric single crystal application parts.
[0071] In addition, the piezoelectric single crystal of the present invention has a high dielectric constant (K T ≧4,000~15,000) and high piezoelectric constant (d 33 ≧1,400~6,000pC / N) at the same time.
[0072] In addition, the piezoelectric single crystal having the composition formula of Chemical Formula 1 of the present invention has a composition gradient of 0.2 to 0.5 mol % within the single crystal, so that a homogeneous single crystal can be provided.
[0073] Lead zirconate (PbZrO3) not only has a high phase transition temperature of 230°C, but also has the effect of making the MPB more perpendicular to the temperature axis, and thus has a high rhombohedral-tetragonal phase transition temperature (T RT ) is obtained, and T C and T RT At the same time, high composition can be developed.
[0074] This is because, even when lead zirconate is mixed into the composition of a conventional piezoelectric single crystal, the phase transition temperature increases in proportion to the content of lead zirconate. Therefore, a piezoelectric single crystal having a perovskite crystal structure containing zirconium (Zr) or lead zirconate can overcome the problems of existing piezoelectric single crystals. In addition, since zirconia (ZrO2) or lead zirconate is used as a main component in existing piezoelectric polycrystal materials and is an inexpensive raw material, the object of the present invention can be achieved without increasing the raw material price of the single crystal.
[0075] In contrast, perovskite type piezoelectric single crystals containing lead zirconate do not show eutectic melting behavior when melted, but show incongruent melting behavior, unlike PMN-PT and PZN-PT. Therefore, if they show incongruent melting behavior, they will separate into liquid and solid phase zirconia (solid phase ZrO2) when melted in solid phase, and the solid phase zirconia particles in the liquid phase will hinder single crystal growth, so they cannot be manufactured by the flux method or Bridgman method, which are general single crystal growth methods that use a melting process.
[0076] In addition, in the general single crystal growth method using a melting process, it is difficult to produce a single crystal containing a reinforcing second phase, and no such method has been reported yet. This is because the reinforcing second phase is chemically unstable and reacts with the liquid phase above the melting temperature, so it cannot maintain an independent second phase morphology and disappears. In addition, due to the density difference between the second phase and the liquid phase in the liquid phase, separation of the second phase and the liquid phase occurs, making it difficult to produce a single crystal containing a second phase, and furthermore, it is not possible to control the volume fraction, size, shape, arrangement, and distribution of the reinforcing second phase inside the single crystal.
[0077] Therefore, the present invention manufactures a piezoelectric single crystal containing a reinforcing second phase by using a solid-phase single crystal growth method that does not use a melting step. In the solid-phase single crystal growth method, the growth of the single crystal is performed at a temperature below the melting temperature, so that the chemical reaction between the reinforcing second phase and the single crystal is suppressed, and the reinforcing second phase can stably exist in an independent form inside the single crystal.
[0078] In addition, the growth of the single crystal is performed on a polycrystalline body containing a reinforcing second phase, and the volume fraction, size, shape, arrangement, distribution, etc. of the reinforcing second phase are not changed during the growth of the single crystal. Therefore, in the process of producing a polycrystalline body containing a reinforcing second phase, if the single crystal is grown while controlling the volume fraction, size, shape, arrangement, distribution, etc. of the reinforcing second phase inside the polycrystalline body, it is possible to manufacture a single crystal containing a reinforcing second phase of a desired shape, i.e., a second phase-reinforced piezoelectric single crystal.
[0079] Therefore, the conventional flux and Bridgman single crystal growth methods cannot manufacture piezoelectric single crystals with a complex composition in the perovskite crystal structure ([A][B]O3). In particular, in the case of the flux and Bridgman methods that include a melting process, the single crystal is manufactured with a composition gradient of 1 to 5 mol % or more in the manufacturing process, whereas the solid phase single crystal growth method of the present invention may manufacture a single crystal with a uniform composition gradient of 0.2 to 0.5 mol % in the inside.
[0080] Therefore, the present invention uses a solid-phase single crystal growth method to grow a piezoelectric single crystal uniformly even when the composition of the [A] site ions and the combination of the [B] site ions are complex in the perovskite crystal structure ([A][B]O3) containing lead zirconate. This allows the piezoelectric single crystal to be grown uniformly, and the dielectric constant (K3 T ≧4,000~15,000), piezoelectric constant (d 33 ≧1,400~6,000pC / N), and coercive electric field (E C It is possible to provide a novel piezoelectric single crystal in which the dielectric constant (Vc) is significantly increased.
[0081] Furthermore, the method for producing a piezoelectric single crystal according to the present invention using the solid phase single crystal growth method allows for mass production at a lower process cost than the flux method and the Bridgman method.
[0082] Specifically, the method for producing a piezoelectric single crystal by the solid phase single crystal growth method of the present invention includes the following steps: (a) adjusting the average size of matrix grains of the polycrystalline body having the composition to reduce the number density of abnormal grains (number of abnormal grains / unit area); (b) heat-treating the polycrystalline body with a reduced number density of abnormal grains obtained by the step (a) to grow the abnormal grains.
[0083] As another manufacturing method, there is provided a method for manufacturing a piezoelectric single crystal, which comprises adjusting the average grain size of matrix grains of a polycrystalline body having the above composition and heat-treating the polycrystalline body under conditions for reducing the number density of abnormal grains.
[0084] In the above, it is possible to obtain a single crystal by continuing to grow only the small number of abnormal grains that have been generated in a state where the number density of abnormal grains in the polycrystalline body has been reduced.
[0085] Before heat-treating the polycrystal, a method for manufacturing a piezoelectric single crystal can be provided in which a seed single crystal is joined to the polycrystal and the seed single crystal is continuously grown in the polycrystal during the heat treatment.
[0086] In the manufacturing method, a powder having a composition constituting the piezoelectric single crystal is calcined at a temperature of 800 to less than 900 °C to obtain a powder compact, and a primary heat treatment step of sintering the powder compact and a secondary heat treatment step during the single crystal growth are used to manufacture the piezoelectric single crystal.
[0087] At this time, it is preferable that the primary and secondary heat treatment steps are performed at 900 to 1,300 °C at a heating rate of 1 to 20 °C / min for 1 to 100 hours. More preferably, the primary heat treatment is performed at 1,000 to 1,200 °C, and then the secondary heat treatment is performed to grow the single crystal.
[0088] The average particle diameter (R) of the matrix particles of the polycrystal is in the range of 0.5 to 2 times the critical particle diameter at which the generation of abnormal grains occurs (the average particle diameter of the matrix particles at which the number density of abnormal grains becomes "0 (zero)", R C ) (0.5R C ≦R≦2R C ). At this time, when the average particle diameter of the matrix particles of the polycrystal is smaller than 0.5R C (0.5R C >R), the number density of abnormal grains is too high, the single crystal does not grow, and when the average particle diameter of the matrix particles of the polycrystal is larger than 2R C (2R C <R), the number density of abnormal grains is "0", but the growth rate of the single crystal is too slow, and a large single crystal cannot be manufactured.
[0089] The present invention provides a piezoelectric body composed of the piezoelectric single crystal alone or a composite of the piezoelectric single crystal and a polymer.
[0090] The polymer is not particularly limited, but as a typical example, when an epoxy resin is mixed, it can be provided in a shape with high resistance to mechanical shock and easy to machine.
[0091] Furthermore, the present invention provides piezoelectric application parts and dielectric application parts using a piezoelectric body made of a perovskite type piezoelectric single crystal having the composition formula of Chemical Formula 1, or a piezoelectric body in which a piezoelectric single crystal is composited with a polymer. Specifically, the piezoelectric application parts include ultrasonic transducers (medical ultrasonic diagnostic equipment, sonar transducers, non-destructive testing transducers, ultrasonic cleaners, ultrasonic motors, etc.), piezoelectric actuators (d 33 Type actuator, d 31 Type actuator, d 15 These include piezoelectric actuators for fine position control, piezoelectric pumps, piezoelectric valves, piezoelectric speakers, etc., piezoelectric sensors (piezoelectric accelerometers, etc.), electric field generating transducers, and electric field and vibration generating transducers.
[0092] Dielectric application parts include high-efficiency capacitors, infrared sensors, and dielectric filters.
[0093] <Example> The present invention will now be described in more detail with reference to examples. These examples are presented to more specifically explain the present invention, and the scope of the present invention is not limited to these examples.
[0094] <Examples 1 to 6> [A] Production of piezoelectric single crystals with complex composition of site ions A piezoelectric single crystal having a perovskite crystal structure ([A][B]O3) was manufactured by a solid phase single crystal growth method. The piezoelectric single crystals of Examples 1 to 6 shown in Table 1 were manufactured, which have a complex composition of the [A] site ions. In addition, in the powder synthesis process, excess MgO and PbO were added so that the inside of the manufactured single crystal contained 2 vol% of the MgO second phase and the pore-strengthening phase. First, MgO and Nb2O5 powders were mixed by ball milling and then calcined to manufacture the MgNb2O6 phase [applied the Columbite method], and additional raw material powders were further mixed in a fixed ratio and calcined to manufacture the perovskite phase powder. Excessive amounts of PbO and MgO were added to the manufactured powder to manufacture a mixed powder. The mixed powder was molded and then press-molded under a hydrostatic pressure of 200 MPa. The powder compacts were heat-treated at various temperatures between 900°C and 1300°C at intervals of 25°C for up to 100 hours. The average grain size (R) of the matrix grains of the polycrystalline bodies was adjusted to a size range (0.5R) between 0.5 and 2 times the critical grain size at which abnormal grains are generated. C ≦R≦2R C The amount of PbO added was determined to be in the range of 10-20 mol%, and the heat treatment temperature was determined to be in the range of 1000-1200°C (first sintering). 0.7 Zr 0.3 A seed single crystal of 03 was placed on the substrate and heat-treated (single crystal growth heat treatment), and a single crystal of a polycrystalline composition was produced by continuously growing the seed single crystal into the polycrystalline body.
[0095] The average grain size (R) of the matrix grains of the polycrystalline body is defined as the critical grain size at which abnormal grains are generated (the average grain size of the matrix grains at which the number density of abnormal grains becomes "0 (zero)", R C ) is in the range of 0.5 to 2 times the size of C ≦R≦2R C), the seed single crystal grew continuously inside the polycrystalline body. In this example, by adjusting the amount of excess PbO and the heat treatment temperature, it was possible to adjust the average grain size (R) of the matrix grains of the polycrystalline body to a size range of 0.5 to 2 times the critical grain size at which abnormal grains are generated. When the average grain size (R) of the matrix grains of the polycrystalline body was adjusted to 0.5R C ≦R≦2R C When the temperature was adjusted to the range of 0.7 Zr 0.3 A single crystal of )O3 seed is continuously grown inside the polycrystal to produce a single crystal with a composition similar to that of a polycrystal. The size of the grown single crystal is 20 x 20 mm. 2 In addition, the piezoelectric single crystal was manufactured by changing the oxygen partial pressure in the atmosphere during the primary sintering of the ceramic powder compact and the heat treatment for single crystal growth.
[0096] <Examples 7-9> [B] Production of piezoelectric single crystals with complex composition of site ions Piezoelectric single crystals of Examples 7 to 9 shown in Table 1 below, which satisfy the composite composition of [B] site ions, were manufactured by the solid phase single crystal growth method as in Example 1. In addition, in the powder synthesis process, excess amounts of MgO and PbO were added so that the inside of the manufactured single crystal contained 2 vol% of MgO second phase and pore-strengthening phase.
[0097] The dielectric and piezoelectric properties of the piezoelectric single crystals of Examples 1 to 9 manufactured by the solid phase single crystal growth method were measured using an impedance analyzer and 33 The analysis was carried out using a meter.
[0098] [Table 1]
[0099] <Experimental Example 1> (Pb, Sr, La) (Mg 1 / 2 Nb 2 / 3 Dielectric and piezoelectric properties of piezoelectric single crystals of )(Zr,Ti)O3 Rating 1 The (Pb, Sr, La)(Mg 1 / 2 Nb2 / 3 Regarding the piezoelectric single crystal of (Zr, Ti)O3, the dielectric and piezoelectric properties of the piezoelectric single crystal manufactured by a / b among the composite compositions of [A] site ions as shown in Table 2 below were evaluated.
[0100] More specifically, the produced [Pb 1-(a+1.5b) Sr a La b ][(Mg 1 / 3 Nb 2 / 3 ) 0.4 Zr 0.25 Ti 0.35 ]O3 (a=0.02; 0.0≦b≦0.1) single crystals, +3 ) content] and a / b [Sr( +2 ) / La( +3 ) ratio] and the dielectric constant and phase transition temperature (T C and T RT ), piezoelectric constant, and coercive field (E C The characteristic changes of each of the above were measured using an impedance analyzer or the like in accordance with the IEEE method, and are shown in Table 2 below.
[0101] [Table 2]
[0102] From the results in Table 2, the piezoelectric charge constant, dielectric constant, and dielectric loss characteristics of the (001) piezoelectric single crystal (a=0.02; b=0.01; a / b=2) were evaluated, and the piezoelectric constant (d 33 ) was 2,650 [pC / N], the dielectric constant was 8,773, and the dielectric loss (tan δ) was 0.5%.
[0103] As a result of the above, b[La( +3 ) content] and a / b [Sr( +2 ) / La( +3) ratio], it has been observed that the physical properties of the piezoelectric single crystal change significantly. In particular, in the composition where "a / b < 2", the growth of the single crystal occurs in a limited manner, and the grown single crystal also contains many defects. Also, in the composition where "a / b < 2", the dielectric loss increases significantly, and the dielectric and piezoelectric constants also decrease significantly.
[0104] Therefore, in the composition region where "a / b ≥ 2", the growth rate of the single crystal and the state of the grown single crystal are relatively excellent. Such results indicate that the piezoelectric single crystal with the "a / b ≥ 2" composition has high practical applicability due to its more excellent piezoelectric properties and single crystal growth characteristics.
[0105] Also, in the manufactured [Pb 1-(a+1.5b) Sr a La b [(Mg 1 / 3 Nb 2 / 3 ) 0.4 Zr 0.25 Ti 0.35 O3 (0.0 < a ≤ 0.15, b = 0.01) single crystal, the characteristic changes of the dielectric constant, phase transition temperatures (T +2 ) content] of a[Sr( +2 ) / La( +3 ) ratio], and the piezoelectric constant and the breakdown electric field (E C and T RT ), were measured by the IEEE method using an impedance analyzer, etc., and are shown in Table 3 below. C )
[0106]
Table 3
[0107] As shown in Table 3 above, the content of a[Sr( +2 )] and a / b[Sr( +2 ) / La( +3It was observed that the physical properties of the piezoelectric single crystal changed significantly depending on the ratio of a / b. In particular, in the case of a composition where a / b<2, the growth of the single crystal was restricted, and the grown single crystal contained many defects. In addition, in the case of a composition where a / b<2, the dielectric and piezoelectric constants also decreased significantly, and the dielectric loss increased significantly.
[0108] Therefore, in the composition region of "a / b ≧ 2," the growth rate of the single crystal and the state of the grown single crystal were relatively excellent. These results indicate that piezoelectric single crystals with a composition of "a / b ≧ 2" have high practical applicability due to their superior piezoelectric properties and single crystal growth characteristics.
[0109] The [Pb 1-(a+1.5b) Sr a La b ][(Mg 1 / 3 Nb 2 / 3 ) 0.4 Zr 0.25 Ti 0.35 In single crystals of ]O3, a[Sr( +2 ) content], b [La( +3 ) content], a / b[Sr( +2 ) / La( +3 When the growth and piezoelectric properties of the piezoelectric single crystal were evaluated according to the change in the ratio of a / b, the growth and physical properties of the single crystal were excellent in the composition ranges of "0.01≦a≦0.10" and "0.01≦b≦0.05". More preferably, when a / b≧2, the most excellent piezoelectric single crystal was developed.
[0110] <Experimental Example 2> (Pb, Ca, Sr, Sm) (Mg 1 / 2 Nb 2 / 3 Dielectric and piezoelectric properties of piezoelectric single crystals of )(Zr,Ti)O3 Rating 2 The [Pb 1-(a+1.5b+c) Ca c Sr a Sm b ][(Mg 1 / 3 Nb 2 / 3 ) 0.35 Zr 0.30 Ti 0.35]O3(0.0≦a≦0.15, 0.0≦b≦0.1, 0.0≦c≦0.1) composition of piezoelectric single crystals, among the composite compositions of [A] site ions, a[Sr( +2 ) content], c[Ca( 2+ ) content], (a+c) / b[(Sr( +2 )+Ca( 2+ )) / Sm( +3 ) ratio] and the dielectric constant and phase transition temperature (T C and T RT ), piezoelectric constant, and coercive field (E C The characteristic changes of each of the above were measured using an impedance analyzer or the like in accordance with the IEEE method, and are shown in Table 4 below.
[0111] [Table 4]
[0112] From the results in Table 4, the piezoelectric charge constant, dielectric constant, and dielectric loss characteristics of the (001) piezoelectric single crystal (a=0.02, b=0.01, c=0.00) were evaluated, and the piezoelectric constant (d 33 ) was 4,457 [pC / N], the dielectric constant was 14,678, and the dielectric loss (tan δ) was 1.0%.
[0113] As shown in Table 4, a[Sr( +2 ) content], c[Ca( 2+ ) content], and (a+c) / b[(Sr( +2 )+Ca( 2+ )) / Sm( +3 It was observed that the physical properties of the piezoelectric single crystal changed significantly depending on the ratio of a+c / b. In particular, in the composition where (a+c) / b<2, the single crystal growth was limited and the grown single crystal contained many defects. In addition, in the composition where (a+c) / b<2, the dielectric loss increased significantly and the dielectric and piezoelectric constants also decreased significantly.
[0114] Therefore, in the composition region of "(a+c) / b≧2", the growth rate of the single crystal and the state of the grown single crystal were relatively excellent. These results indicate that the piezoelectric single crystal with the composition of "(a+c) / b≧2" has high practical applicability due to its superior piezoelectric properties and single crystal growth characteristics.
[0115] In addition, the [Pb 1-(a+1.5b+c) Ca c Sr a Sm b ][(Mg 1 / 3 Nb 2 / 3 ) 0.35 Zr 0.30 Ti 0.35 ]O3 (0.0≦a≦0.15, 0.0≦b≦0.1, c=0.01) single crystals, a[Sr( +2 ) content], b [Sm( 3+ ) content], and (a+c) / b[(Sr( +2 )+Ca( 2+ )) / Sm( +3 ) ratio] and the dielectric constant and phase transition temperature (T C and T RT ), piezoelectric constant, coercive electric field (E C The characteristic changes of each of the above were measured using an impedance analyzer or the like in accordance with the IEEE method, and are shown in Table 5 below.
[0116] [Table 5]
[0117] As shown in Table 5, in the single crystal, a[Sr( +2 ) content], b [Sm( 3+ ) content], and (a+c) / b[(Sr( +2 )+Ca( 2+ )) / Sm( +3It was observed that the physical properties of the piezoelectric single crystal changed significantly depending on the ratio of (a+c) / b. In particular, in the composition where (a+c) / b<2, the growth of the single crystal was restricted, and the grown single crystal contained many defects. In addition, in the composition where (a+c) / b<2, the dielectric loss increased significantly, and the dielectric and piezoelectric constants also decreased significantly.
[0118] Therefore, in the composition region of "(a+c) / b≧2", the growth rate of the single crystal and the state of the grown single crystal were relatively excellent. These results indicate that the piezoelectric single crystal with the composition of "(a+c) / b≧2" has high practical applicability due to its superior piezoelectric properties and single crystal growth characteristics.
[0119] In addition, the [Pb 1-(a+1.5b+c) Ca c Sr a Sm b ][(Mg 1 / 3 Nb 2 / 3 ) 0.35 Zr 0.30 Ti 0.35 ]O3(0.0≦a≦0.15, 0.0≦b≦0.1, 0.0≦c≦0.1) single crystals, a[Sr( +2 ) content], b [Sm( +3 ) content], c[Ca[ +2 When the growth and piezoelectric properties of the piezoelectric single crystal were evaluated according to the change in the content of and (a+c) / b, the single crystal growth and properties were excellent in the composition ranges of 0.01≦(a+c)≦0.10 and 0.01≦b≦0.05. More preferably, when (a+c) / b≧2, the best piezoelectric single crystal was developed.
[0120] <Experimental Example 3> (Pb, Ni, Sm) (Mg 1 / 2 Nb 2 / 3 Dielectric and piezoelectric properties of piezoelectric single crystals of )(Zr,Ti)O3 Rating 3 The [Pb 1-(a+1.5b) Ni a Sm b ][(Mg 1 / 3 Nb 2 / 3 )0.35 Zr 0.30 Ti 0.35 ]O3 (0.0≦a≦0.15, 0.0≦b≦0.1) composition, the dielectric constant, piezoelectric constant, and electromechanical coupling coefficient (k 33 The characteristic changes of each of the above were measured using an impedance analyzer or the like in accordance with the IEEE method, and are shown in Table 6 below.
[0121] [Table 6]
[0122] As shown in Table 6, it was observed that the physical properties of the piezoelectric single crystal changed significantly depending on the change in a [Ni content] and a / b [Ni / Sm ratio]. In particular, in the composition where a / b<2, the single crystal growth was restricted and the grown single crystal contained many defects. In addition, in the composition where a / b<2, the dielectric loss increased significantly and the dielectric and piezoelectric constants also decreased significantly.
[0123] Therefore, in the composition region of "a / b≧2," the growth rate of the single crystal and the state of the grown single crystal were relatively excellent. These results indicate that the piezoelectric single crystal with the composition of "a / b≧2" has high practical applicability due to its superior piezoelectric properties and single crystal growth characteristics.
[0124] In addition, the [Pb 1-(a+1.5b) Ni a Sm b ][(Mg 1 / 3 Nb 2 / 3 ) 0.35 Zr 0.30 Ti 0.35When the growth and piezoelectric properties of the piezoelectric single crystals of ]O3 (0.0≦a≦0.15, 0.0≦b≦0.1) were evaluated according to the change in a [Ni content], b [Sm content], and a / b, the single crystal growth and physical properties were excellent in the composition ranges of "0.01≦a≦0.10" and "0.01≦b≦0.05". More preferably, when a / b≧2, the best piezoelectric single crystals were developed.
[0125] <Experimental Example 4> (Pb, Sr, Bi) (Mg 1 / 2 Nb 2 / 3 Dielectric and piezoelectric properties of piezoelectric single crystals of )(Zr,Ti)O3 Rating 4 The [Pb 1-(a+1.5b) Sr a Bi b ][(Mg 1 / 3 Nb 2 / 3 ) 0.35 Zr 0.30 Ti 0.35 ]O3 (0.0≦a≦0.15, 0.0≦b≦0.1) composition, the dielectric constant, piezoelectric constant, and electromechanical coupling coefficient (k 33 The characteristic changes of each of the above were measured using an impedance analyzer or the like in accordance with the IEEE method, and are shown in Table 7 below.
[0126] [Table 7]
[0127] As shown in Table 7, it was observed that the physical properties of the piezoelectric single crystal changed significantly depending on the change in a [Sr content] and a / b [Sr / Bi ratio]. In particular, in the composition where a / b<2, the single crystal growth was restricted and the grown single crystal contained many defects. In addition, in the composition where a / b<2, the dielectric loss increased significantly and the dielectric and piezoelectric constants also decreased significantly.
[0128] Therefore, in the composition region of "a / b ≧ 2," the growth rate of the single crystal and the state of the grown single crystal were relatively excellent. These results indicate that piezoelectric single crystals with a composition of "a / b ≧ 2" have high practical applicability due to their superior piezoelectric properties and single crystal growth characteristics.
[0129] In addition, the [Pb 1-(a+1.5b) Sr a Bi b ][(Mg 1 / 3 Nb 2 / 3 ) 0.35 Zr 0.30 Ti 0.35 When the growth and piezoelectric properties of the piezoelectric single crystal were evaluated for single crystals of ]O3 (0.0≦a≦0.15, 0.0≦b≦0.1) with a [Sr content], b [Bi content], and a / b, the single crystal growth and physical properties were excellent in the composition ranges of "0.01≦a≦0.10" and "0.01≦b≦0.05". More preferably, when a / b≧2, the best piezoelectric single crystal was developed.
[0130] <Experimental Example 5> (Pb, Sr, Sm) (Mg 1 / 2 Nb 2 / 3 Dielectric and piezoelectric properties of piezoelectric single crystals of )(Zr,Hf)TiO3 Rating 5 The [Pb 0.98-1.5x Sr a Sm b ][(Mg 1 / 3 Nb 2 / 3 ) 0.35 (Zr 1-x Hf x ) 0.30 Ti 0.35 ]O3 (0.0≦a≦0.15, 0.0≦b≦0.1, 0.0≦x≦0.5) piezoelectric single crystals, the dielectric constant, piezoelectric constant, and electromechanical coupling coefficient (k 33 The characteristic changes of each of the above were measured using an impedance analyzer or the like in accordance with the IEEE method, and are shown in Table 8 below.
[0131] [Table 8]
[0132] As shown in Table 8, it was observed that the physical properties of the piezoelectric single crystal changed significantly depending on the changes in a [Sr content], b [Sm content], a / b [Sr / Sm ratio], and x [Hf content]. In particular, in the composition where "0.0≦x≦0.5", the single crystal grew faster and the defects in the grown single crystal were reduced. In addition, in the composition where "0.0≦x≦0.2", the dielectric and piezoelectric constants also increased. These results indicate that the piezoelectric single crystal in the composition where "0.0≦x≦0.5" has better piezoelectric properties and single crystal growth properties, making it more practically applicable.
[0133] <Experimental Example 6> (Pb, Ni, Sm) (Mg 1 / 2 Nb 2 / 3 Dielectric and piezoelectric properties of piezoelectric single crystals of )(Zr,Hf)TiO3 Rating 6 The [Pb 0.98-1.5x Ni a Sm b ][(Mg 1 / 3 Nb 2 / 3 ) 0.35 (Zr 1-x Hf x ) 0.30 Ti 0.35 ]O3 (0.0≦a≦0.1, 0.0≦b≦0.1, 0.0≦x≦0.5) for which the dielectric constant, piezoelectric constant, and electromechanical coupling coefficient (k 33 The characteristic changes of each of the above were measured using an impedance analyzer or the like in accordance with the IEEE method, and are shown in Table 9 below.
[0134] [Table 9]
[0135] As shown in Table 9, it was observed that the physical properties of the piezoelectric single crystal changed significantly depending on the changes in a [Ni content], b [Sm content], a / b [Ni / Sm ratio], and x [Hf content]. In particular, in the composition "0.0≦x≦0.5", the single crystal grew faster and the defects in the grown single crystal were reduced. In addition, in the composition "0.0≦x≦0.2", the dielectric and piezoelectric constants also increased. These results indicated that the piezoelectric single crystal in the composition "0.0≦x≦0.5" has better piezoelectric properties and single crystal growth properties, making it more practically applicable.
[0136] <Experimental Example 7> Measurement of breaking strength The [Pb 1-(a+1.5b) Sr a La b ][(Mg 1 / 3 Nb 2 / 3 ) 0.4 Zr 0.25 Ti 0.35 For piezoelectric single crystals with a composition of ]O3 (0.0≦a≦0.15, b=0.01), mechanical properties such as fracture strength and fracture toughness depending on the pore content in the single crystal were compared and evaluated. At this time, the fracture strength value was measured by a four-point bending strength measurement method according to the ASTM method, and the results are shown in the following Table 10 (a=0.02, b=0.01) and Table 11 (a=0.04, b=0.01).
[0137] [Table 10]
[0138] [Table 11]
[0139] From the above results, the [Pb 1-(a+5b) S a La b ][(Mg 1 / 3 Nb 2 / 3 ) 0.4 Zr0.25 Ti 0.35 ]O3 (0.0≦a≦0.15, b=0.01) piezoelectric single crystals showed a tendency for fracture strength and fracture toughness to increase when they contained pores inside the single crystal, and showed high fracture strength and fracture toughness values when the pore content was within 20%. In particular, the closer the shape of the pores was to a spherical shape, the greater the effect of improving the mechanical properties. Therefore, when pores and a reinforcing phase such as MgO are contained inside the single crystal, the resistance of the single crystal to external mechanical shocks increases, and as a result, the mechanical performance of the single crystal of the composite was greatly improved.
[0140] Based on the above results, the piezoelectric properties were maximized through the composition of the piezoelectric single crystal, and the mechanical properties of the single crystal were enhanced using a reinforcing phase, thereby maintaining the high piezoelectric properties of the piezoelectric single crystal and improving the mechanical brittleness properties, resulting in the creation of a piezoelectric single crystal that is excellent in both properties.
[0141] Although the present invention has been described in detail above only with reference to the specific examples, it will be apparent to those skilled in the art that various modifications and variations are possible within the scope of the technical concept of the present invention, and these modifications and variations are included in the scope of the appended claims.
Claims
1. The following chemical formula 1: Chemical formula 1 [A 1-(a+1.5b) B a C b ][(MN) 1-x-y (L) y Ti x ]O 3 (In the above formula, A is Pb or Ba; B is at least one selected from the group consisting of Ba, Ca, Co, Fe, Ni, Sn, and Sr; C is at least one selected from the group consisting of Co, Fe, Bi, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu; L is selected from Zr or Hf, either alone or in a mixed form; M is at least one selected from the group consisting of Ce, Co, Fe, In, Mg, Mn, Ni, Sc, Yb, and Zn; N is at least one selected from the group consisting of Nb, Sb, Ta, and W; 0<a≦0.10, 0<b≦0.05, 0.05≦x≦0.58, and 0.05≦y≦0.62). It has a perovskite structure and a composition formula of A piezoelectric single crystal characterized by:
2. In the piezoelectric single crystal, L is a mixed type and has the following formula 2: chemical formula 2 [A 1-(a+1.5b) B a C b ][(MN) 1-x-y (Zr) 1-w ,Hf w ) y Ti x ]O 3 (In the above formula, 0.01≦w≦0.20) having the formula The piezoelectric single crystal according to claim 1:
3. In the above formula, 0.01≦a≦0.10, 0.01≦b≦0.
05. The piezoelectric single crystal according to claim 1 .
4. In the above formula, a / b≧2. The piezoelectric single crystal according to claim 1 .
5. In the above formula, 0.10≦x≦0.58 and 0.10≦y≦0.
62. The piezoelectric single crystal according to claim 1 .
6. The piezoelectric single crystal has an internal composition gradient of 0.2 to 0.5 mol %. The piezoelectric single crystal according to claim 1 .
7. The composition of the piezoelectric single crystal further includes a reinforcing second phase (P) of 0.1 to 20% by volume. The piezoelectric single crystal according to claim 1 .
8. The reinforcing second phase (P) is a metal phase, an oxide phase, or a pore. The piezoelectric single crystal according to claim 7.
9. The strengthening second phase (P) is Au, Ag, Ir, Pt, Pd, Rh, MgO, ZrO 2 and pores. The piezoelectric single crystal according to claim 8.
10. The reinforcing second phase (P) is distributed uniformly in a particulate form or regularly in a certain pattern within the piezoelectric single crystal. The piezoelectric single crystal according to claim 8.
11. The x and y are within a range of 10 mol % from the composition of the phase boundary (MPB) between the rhombohedral phase and the tetragonal phase. The piezoelectric single crystal according to claim 1 .
12. The x and y are within a range of 5 mol % from the phase boundary (MPB) composition between the rhombohedral phase and the tetragonal phase. The piezoelectric single crystal according to claim 1 .
13. The piezoelectric single crystal has an electromechanical coupling coefficient (k 33 ) is 0.85 or more The piezoelectric single crystal according to claim 1 .
14. A method for producing a piezoelectric single crystal according to claim 1, comprising the steps of: (a) calcining a powder having a composition constituting the piezoelectric single crystal according to claim 1 at a temperature of 800 to 900° C. or less to obtain a powder, and performing a primary heat treatment process of sintering the powder to adjust the average size of matrix grains of a polycrystalline body having a composition constituting the piezoelectric single crystal and reduce the number density of abnormal grains / unitarea; (b) heat-treating the polycrystalline body with a reduced number density of abnormal grains obtained by step (a) to grow the abnormal grains to obtain a single crystal, and performing a secondary heat-treatment process during the growth. A method for producing a piezoelectric single crystal comprising the steps of:
15. The first and second heat treatment processes are carried out at 900 to 1,300° C. The method for producing a piezoelectric single crystal according to claim 14.
16. The heat treatment is carried out at a heating rate of 1 to 20° C. / min for a period of 1 to 100 hours. The method for producing a piezoelectric single crystal according to claim 15.
17. The average grain size (R) of the matrix grains of the polycrystalline body is the critical grain size at which abnormal grains are generated (the average grain size of the matrix grains at which the number density of abnormal grains becomes "0 (zero)", R C ) to 0.5 to 2 times the size range (0.5R C ≦R≦2R C ) is adjusted within The method for producing a piezoelectric single crystal according to claim 14.
18. A piezoelectric body made of the piezoelectric single crystal according to any one of claims 1 to 13, or a piezoelectric body made by combining the piezoelectric single crystal and a polymer. A piezoelectric or dielectric applied component characterized in that:
19. The piezoelectric or dielectric applied part is any one selected from the group consisting of ultrasonic transducers, piezoelectric actuators, piezoelectric sensors, dielectric capacitors, electric field generating transducers, and electric field and vibration generating transducers.
19. A piezoelectric or dielectric applied part according to claim 18.
Citation Information
Patent Citations
Perovskite type oxide, piezoelectric element, liquid discharge head and liquid discharge apparatus using the same, and method of producing perovskite type oxide
JP2007084424A
Piezoelectric single crystal and method for manufacturing the same, as well as piezoelectric and dielectric application components utilizing the piezoelectric single crystal.
JP2009514765A
Piezoelectric ceramic composition, piezoelectric ceramic, piezoelectric element and oscillator
JP2011068516A
Method for the Solid-State Single Crystal Growth
KR100564092B1
Piezoelectric Single Crystal and Method of Production of Same, Piezoelectric Element, and Dielectric Element
KR100743614B1